METHODOLOGY FOR THE DEVELOPMENT OF PROFESSIONAL AND PEDAGOGICAL SKILLS OF FUTURE MUSIC EDUCATION TEACHERS BASED ON FORWARD-LOOKING VIEWS (Scientific journal of the Fergana State University, 2024)
There is an increasing need to improve the system aimed at developing professional and pedagogical skills in music education. A systematic approach to the process of educating the younger generation through the art of music and singing is characterized by its purposefulness and consistency. In this sense, this article reveals the musical views of Abu Nasr Farabi and their significance in the development of pedagogical skills among future music education teachers.